The 'last words'. The notary’s mediating role in the end of life (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The fundamental role of the notary as mediator in drafting wills is analyzed through the rich collection of notarial documents dating from the 12th and 13th centuries and preserved in the Archivio di Stato di Genova. The registers that have come down to us contain numerous last wills structured according to the so-called Bolognese model and thus offer the possibility of observing these professionals at work from the second half of the 12th century onward, precisely when the Roman will was rediscovered.
Keywords: Wills; Notarial mediation; Genoa; 12th-13th Centuries